The Efficiency Analysis of Government Expenditure on Education and Health in Sumatra: The DEA Approach - Sanya Hibatulmedina; Roosemarina Anggraini Rambe (Department of Development Economics, Universitas Sriwijaya, 2021)
The purposes of this study are to measure the level of the relative efficiency of educational spending and healthcare spending in achieving Mean Years of Schooling (MYS) and life expectancy at regency and city in Sumatera. Data Envelopment Analysis (DEA) were employed for a data set of the spending of 154 local governments in 2019 with an output-oriented model. The approach used is a variable return to scale. In measuring efficiency, two input were used are (i) Government spending of the educational function and (ii) Government spending of the healthcare function, while two output were used are (i) Mean Years of Schooling (MYS) and (ii) life expectancy. The results show that, of the 154 local governments, 6 across ten regency and city in Sumatra, were relatively efficient. There are Gunungsitoli, Bukit Tinggi, Padang Panjang, Solok, Banda Aceh and West Nias.